EDM473 : Educational marketing / Faculty of Education - UiTM, Faculty of Education (Universiti Teknologi MARA (UiTM), 2023)
Services, products and privileges of education need to be disseminated via strategic educational marketing. This strategy is to ensure that society benefits from the marketed educational institution. Special focus is given to educational marketing models and its application to Malaysian schools. The focus of the study will be on elite schools, MRSM, polytechnics, technical schools and smart schools.